Collaborative design for metadata interoperability in webopac - Abdul Rashid, Naizura; Mansor, Yushiana (Persatuan Pustakawan Malaysia, 2014)
Most system metadata development in Malaysian libraries deploys a top-down approach in which actual users were not involved. This resulted in the failure of the system to adequately meet the users’ pragmatic needs. As studies on metadata pragmatic used are rare in the library bibliographic databases, this study investigated common system metadata elements used by Malaysian libraries in describing information objects in the domain of banking and finance, and the preferred user metadata elements in locating the needed information. Specifically, this study addresses two important questions, namely (1) what are the metadata elements preferred by users when searching for library resources on Islamic finance, and (2) how compatible are the system metadata with preferred user metadata elements? This study deployed the conceptual framework of collaborative metadata approach to identify compatibility elements between user metadata and system metadata.